THE EFFECT OF DISCIPLINE AND MOTIVATION ON STUDENT LEARNING ACHIEVEMENT (Study at Harapan Umat Arongan Private Middle School) - Nurul Izzati; Afra Fadhilah; Rosdiana; Fais Al Hadi; M Saifrizal (Universitas Efarina, 2022)
This research aims to analyze the influence of discipline on student learning achievement at Harapan Umat Arongan Private Middle School, the influence of motivation on student learning achievement at Harapan Umat Arongan Private Middle School and the influence of discipline and motivation on student learning achievement at Harapan Umat Arongan Private Middle School. In this research, researchers used quantitative research. The sample in this study was 65 students at Harapan Umat Arongan Private Middle School. The results of this research show that the results of the t test on the discipline variable (X1) obtained tcount > ttable (5.166 > 1.998) with a probability of 0.000 whose value is below 0.05. Thus Ha1 is accepted, which means that there is a partially significant positive influence of discipline (X1) on student learning achievement (Y) at Harapan Umat Arongan Private Middle School. The results of the t test on the learning motivation variable (X2) obtained tcount > ttable (4.146 > 1.998) with a probability of 0.000 with a value below 0.05. Thus, Ha2 is accepted, which means that there is a partially significant positive influence on learning motivation (X2) on student learning achievement (Y) at Harapan Umat Arongan Private Middle School. The results of the calculation of Fcount ˃ Ftable (8.023 ˃ 2.75) obtained a sig value (0.000 ˂ 0.05), so simultaneously (together) discipline (X1) and learning motivation (X2) have a significant effect on learning achievement (Y) students at Harapan Umat Arongan Private Middle School.